Jet Fuel Toxicology - Witten, Mark L [Ed.]; Zeiger, Errol [Ed.]; David Ritchie,Glenn [Ed.] (Newyork : CRC Press, 2011)
Currently serving as a resource for the National Center for Toxological Research in their work with the Gulf Coast oil spill, this book presents current research conducted primarily by the airforce on the toxic effects of JP-8 jet fuel on the pulmonary, immune, dermal, and nervous systems. In all, the book considers 13 toxicology studies of significance, the results of which are currently shaping US armed services policy. It will enable all of the hydrocarbon industry to make better choices regarding fuel handling.Due to its widespread use, jet fuel is thought to be the largest toxicant exposure risk for U.S. Armed Services personnel. Taking a proactive approach to the potential dangers of repeated human exposure to hydrocarbon fuels, the Air Force Office of Scientific Research (AFOSR) sponsored a number of research projects during the last 20 years investigating health effects resulting from specific exposure to JP-8 (Jet Propellant-8). Jet Fuel Toxicology summarizes the newest and most important results of these extensive research programs carried out by hydrocarbon fuel research groups throughout the U.S. Each book chapter highlights one specific research area from the many topical areas comprising jet fuel toxicology. After examining the contents and general action of JP-8, the book looks at how the fuel affects various body functions highlighted by: Effects on daily inhalation on the respiratory system Acute and long-term neurotoxicological and neurobehavioral effects Both local and systemic toxicity following exposure through the skin Immunotoxicity from pulmonary and dermal exposures Genetic damage, as evidenced in studies of the blood and bone marrow of mice In all, the book considers 13 major toxicology areas of study, the results of which will enable all of the hydrocarbon industry to make
Keywords: Toxicology